Kosovo : Economic Memorandum - World Bank (Washington, DC, 2013)
Prospects for economic growth depend upon the success of two overarching factors (1) mitigating risks related to political uncertainty and the maintenance of peace and security in the region; and (2) implementation of a policy program that promotes private sector- led growth, including completion of the reconstruction effort. Such a package of reforms might include the following measures: Within a sound fiscal position proceed with prioritized capital projects to complete the rehabilitation of infrastructure, but resist unsustainable spending on recurrent expenses such as the public sector wage bill. Pursue improved trade relations within the region. Maintain a uniform tariff rate and reduce the rate across the board. Consider a compensating revenue effort to raise taxes from the value-added tax, including through improved administration. Proceed with privatization of socially-owned enterprises and restructuring of publicly owned enterprises, including privatization of land-use rights of public enterprises (SOEs) slated for liquidation. Strengthen the capacity of the municipal courts to implement and enforce creditors rights and contracts. Rehabilitate the power sector, including lignite mines, and pursue a strategy for integrating with the regional power grid. Develop a strategy for the revitalization of the rest of the mining sector. Address overstaffing issues in private enterprises and SOEs, address transitional unemployment issues and facilitate redeployment to alternative productive activities. Keep the labor market relatively unencumbered by payroll taxes. Facilitate employment search. by linking information systems to enterprise surveys and the provision of vocational training. and then looking at the particulars of several sectors. Chapter 2 looks at macroeconomic stability, and considers the prospects for improving economic growth in Kosovo. Chapter 3 discusses a conducive business Climate. Chapter 4 examines the prospects for export-led growth in the power, mining and agriculture sectors. These are three sectors in which Kosovo could have a comparative advantage, as it is relatively well endowed with (1) lignite, (2) other minerals, and (3) fertile agricultural land; enjoys free trade with the European Union and is geographically located close to Western European markets. Finally, Chapter 5 reviews the labor market outcomes and policies for a liberal labor market and an appropriately skilled labor force.